2018
DOI: 10.1111/are.13606
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fasting and feeding on growth, intestinal morphology and enteroendocrine cell density in Rhamdia quelen juveniles

Abstract: This study was carried out to assess the effect of fasting and feeding on growth, intestinal morphology and density of cholecystokinin (CCK‐) and neuropeptide Y (NPY‐) immunoreactive cells in Rhamdia quelen. Fish were fed during 30 days with three commercial feeds containing different protein levels (T1 = 25%, T2 = 30% and T3 = 45%) while one group remained food deprived (T0). Our results show that the T3 group presented higher final mean weight and specific growth rate, while food‐deprived group showed a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 70 publications
1
9
0
1
Order By: Relevance
“…This ability to withstand fasting probably influenced the survival values observed in the present experiment. As in the present experiment, several other authors have reported little or no mortality in fasting experiments conducted on fish (Power et al 2000, Hernández et al 2018.…”
Section: Survival Estimatesupporting
confidence: 78%
See 1 more Smart Citation
“…This ability to withstand fasting probably influenced the survival values observed in the present experiment. As in the present experiment, several other authors have reported little or no mortality in fasting experiments conducted on fish (Power et al 2000, Hernández et al 2018.…”
Section: Survival Estimatesupporting
confidence: 78%
“…These animals obtain the energy necessary for their basal metabolism, physical activities, growth, and reproduction from food intake (Wang et al 2006). When food is not available, they must use their energy reserves to survive (Urbinati et al 2014, Hernández et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…The digestive tract of fish exhibits a certain phenotypic plasticity in response to changes in diet and feeding (Buddington & Hilton, 1987;Buddington et al, 1997). The absence of morphological changes in the intestines of pirarucus fed with frozen zooplankton is another sign that the food presented nutritional composition and intake similar to live zooplankton (Hernández et al, 2018), even accompanying the growth of fish over the 18 days of the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…The digestive tract of fish exhibits a certain phenotypic plasticity in response to changes in diet and feeding (Buddington & Hilton, 1987; Buddington et al, 1997). The absence of morphological changes in the intestines of pirarucus fed with frozen zooplankton is another sign that the food presented nutritional composition and intake similar to live zooplankton (Hernández et al, 2018), even accompanying the growth of fish over the 18 days of the experiment. In addition, during the short period of experimentation, both live and frozen zooplankton increased the height of intestinal folds and the intestinal absorption surface, suggesting that natural zooplankton is suitable as the first food for pirarucu.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, García-Meilán et al [ 21 ] showed seasonal differences with higher digestive enzyme synthesis and food intake in spring, due to the longer photoperiod in comparison to autumn. In winter, wild fish can stand fasting for a relatively long time lapse, with changes of gut morphology and a reduction of 20–75% of digestive enzymatic activity [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%